(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the study of paper with high strength on the basis of domestic raw materials, the article studied the effect of the concentration of filler in the composite composition containing a cotton cellulose paper of high quality and hydrolyzed acrylic sopolymer, and the ph of the pulp to the paper breaking length cast. It was established a reduction in paper strength with increasing amounts of filler, and weakly acidic medium to increase this figure. The composite structure based on domestic raw materials will reduce the cost of paper production.